Myeloperoxidase/paraoxonase ratio as a prognostic marker for post-COVID syndrome in patients undergoing hemodialysis: A cross-sectional cohort study - Korol, L.; Stepanova, N.; Popova, O.; Malashevska, N.; Vasylchenko, V.; Ostapenko, T.; Rysyev, A.; Kolesnyk, M. (Ukrainian Journal of Nephrology and Dialysis, 2023)
The present study aimed to assess the impact of post-COVID syndrome on the oxidative status and activity of paraoxonase 1 (PON-1), myeloperoxidase (MPO), and leukocyte elastase in the blood of patients undergoing hemodialysis (HD). Methods. In this cross-sectional cohort study, 290 patients undergoing HD were included. The oxidative status was assessed based on the levels of blood malondialdehyde (MDA), ceruloplasmin, thiol compounds (SH-groups), and the serum activities of myeloperoxidase (MPO), paraoxonase-1 (PON-1), and elastase were determined. Results. It was found that HD patients exhibited an elevation in oxidative processes, characterized by increased blood concentrations of MDA, MPO, elastase activity, and a decrease in the levels of SH-groups and arylesterase activity of PON-1. Patients with post-COVID syndrome showed further increases in MPO activity and a decrease in arylesterase activity of PON-1. Additionally, a statistically significant elevation in the MPO/PON-1 ratio was observed in HD patients with post-COVID syndrome compared to the control group and patients examined before the onset of the pandemic (p < 0.0001). The MPO/PON-1 ratio exhibited a direct correlation with serum MDA levels (p < 0.0001) and inversely correlated with the concentration of ceruloplasmin (p = 0.0008). The MPO/PON-1 value surpassing 9.06 units was identified as a predictive marker for PCS, demonstrating a specificity of 68.4% and a sensitivity of 88.5%. Conclusions. Our study highlights a significant impact of post-COVID syndrome on oxidative processes in HD patients, as evidenced by elevated MDA levels and MPO activity, along with reduced levels of antioxidants and arylesterase activity of PON-1. The MPO/PON-1 ratio emerges as a promising predictive marker for post-COVID syndrome, underlining its potential clinical relevance in identifying at-risk patients.